CHILD PROTECTION STRATEGIES AT AGRARIAN CONFLICT AREA (A Case Study at Moro-Moro Village, Register 45, Mesuji Regency) - Wijatnika, Wijatnika (JURNAL SOSIOLOGI, 2014)
Moro-Moro community understands that education is one of the most important parts of human basic right, especially at agrarian conflict area. There are several points that Moro-Moro community provides for child protection by education: 1) established school committee and gained some voluntary teachers, 2) established some school buildings, 3) integrates system to âmain office, 4) finding scholarship for some students who continue to higher education, and) send back some graduates to teach at some school at Moro-Moro. This paper is aim to explain those points as fundamental strategies to actualize child welfare at agrarian conflict area.